The influencing factors of participation in time banking volunteer service for older adults among university students in Nanjing, China - Wu, Yue; Liu, Siyu; Song, Yating; Zhang, Zhirui; Liu, Yunlong (Frontiers in Public Health, 2024)
Objective: This study aims to identify factors influencing university students' participation in time banking elderly volunteer services and provides evidence to promote involvement.Conducted in November 2022, we utilized a convenience sampling method to recruit students from the School of Elderly Care Service and Management at Nanjing University of Chinese Medicine, China. Data was collected through an online questionnaire focusing on various aspects related to time banking elderly volunteer services. Factor analysis was employed to extract variables, and logistic regression was applied to identify key determinants.Results: A significant majority (82.67%) of participants expressed willingness to engage in elderly volunteer services. Factor analysis uncovered six influential factors explaining 62.55% of the variance. Logistic regression highlighted four key determinants of students' willingness: value judgment (OR=4.392, CI=2.897-6.658), social support (OR=1.262, CI=0.938-1.975), social influence (OR=1.777, CI=1.598-3.799), and socioeconomic conditions (OR=1.174, CI=1.891-3.046).To foster sustainability and continuous time banking among elderly care services and management major university students, a multifaceted support involving governmental, social, and university is recommended.